2020
DOI: 10.1371/journal.pgen.1008743
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape of metastasis in treatment-naïve breast cancer models

Abstract: Metastasis remains the principle cause of mortality for breast cancer and presents a critical challenge because secondary lesions are often refractory to conventional treatments. While specific genetic alterations are tightly linked to primary tumor development and progression, the role of genetic alteration in the metastatic process is not well-understood. The theory of tumor evolution postulated by Peter Nowell in 1976 has yet to be proven in the context of metastasis. Therefore, in order to investigate how … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 73 publications
(85 reference statements)
1
21
0
Order By: Relevance
“…While these tumors maintain their diploid status, amplifications and deletions have been reported [13]. For example, amplifications of chromosome 11 are common in these tumors [13][14][15][16][17]. Chromosome 11 is orthologous to chromosome 17 in humans, which is commonly amplified and associated with increased PI3K activity due to amplification of the ErbB2 locus [15][16][17][18].…”
Section: The Pymt Gemms Faithfully Recapitulate Human Breast Cancer Pmentioning
confidence: 99%
See 2 more Smart Citations
“…While these tumors maintain their diploid status, amplifications and deletions have been reported [13]. For example, amplifications of chromosome 11 are common in these tumors [13][14][15][16][17]. Chromosome 11 is orthologous to chromosome 17 in humans, which is commonly amplified and associated with increased PI3K activity due to amplification of the ErbB2 locus [15][16][17][18].…”
Section: The Pymt Gemms Faithfully Recapitulate Human Breast Cancer Pmentioning
confidence: 99%
“…Several subsequent studies revealed that the expression of the PyMT oncogene is coupled to additional biochemical and genetic events that drive tumorigenesis and metastasis [ 12 ]. To that end, genomic analysis and whole exome sequencing was performed on the arising tumors [ 13 , 14 ]. While these tumors maintain their diploid status, amplifications and deletions have been reported [ 13 ].…”
Section: The Pymt Gemms Faithfully Recapitulate Human Breast Cancer Pmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathways were subsequently validated as key metastasis-modifying pathways in allograft transplantation models, using therapeutically relevant dosing schemas. These gene expression pathways are also enriched in lung metastases from three breast cancer patient-derived xenograft models generated by Alzubi and colleagues (29,42), providing further support of their relevance to human breast cancer metastasis. The molecular target of sildenafil, phosphodiesterase type 5 (PDE5) has been identified as a tumor biomarker in several human cancers (43,44), and work with human cancer cell lines has revealed that expression and activation of PDE5 stimulates invasive, migratory, and cancer stem cell phenotypes (44).…”
Section: T1mentioning
confidence: 69%
“…A study that conducted WES of paired primary tumors and lung metastases from the MMTV-PyMT and MMTV - Her2 models identified metastasis-enriched and metastasis-specific mutations and CNAs in known oncogenes, including Kras. Orthotopic engraftment of cells expressing the Kras G12D mutation led to increased metastatic burden while knock down of Kras reduced metastasis to the lungs [ 126 ].…”
Section: Bulk Analysis Of Ith In Laboratory Modelsmentioning
confidence: 99%